2011
DOI: 10.1002/pbc.23078
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in cancer outcomes: Lessons learned from children with cancer

Abstract: Disparities in cancer burden by race/ethnicity have been reported, primarily in adults with cancer. However, there appear to be gaps in the pediatric oncology literature with regards to a comprehensive overview on this topic. Extant literature is used to highlight the results of studies focusing on racial and ethnic disparities in outcome observed in selected childhood cancers. A comprehensive approach is utilized to understand possible underlying causes of disparities in cancer outcomes, and to highlight the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
191
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(202 citation statements)
references
References 58 publications
6
191
2
2
Order By: Relevance
“…And the lower cancer rates in Maroons -the second largest ethnic group is Suriname [22] -when compared to the other ethnic groups may be explained by the limited diagnostic and health care facilities in the interior of Suriname where many of them live [22]. Notably, several studies (see for instance references [45,46]) have found that differential inclusion of racial groups in cancer registries may represent a potential source of bias in the interpretation of the results of cancer prevalence studies.…”
Section: Discussionmentioning
confidence: 99%
“…And the lower cancer rates in Maroons -the second largest ethnic group is Suriname [22] -when compared to the other ethnic groups may be explained by the limited diagnostic and health care facilities in the interior of Suriname where many of them live [22]. Notably, several studies (see for instance references [45,46]) have found that differential inclusion of racial groups in cancer registries may represent a potential source of bias in the interpretation of the results of cancer prevalence studies.…”
Section: Discussionmentioning
confidence: 99%
“…SEER data are used widely as a bench-mark data source for studying PNCT outcomes in US and in other countries (Perme and Jereb, 2009;Lacour et al, 2010;Johnson et al, 2011). The extensive ground coverage by the SEER data is ideal for identifying the disparity in oncology outcome and treatment in different geographical and cultural areas for cancers (Bhatia, 2011;Johnson et al, 2011;Pui et al, 2012). In addition to the biological staging factors and the treatment factors, this database also contains a large number of county level socio-economic factors data.…”
Section: Poor Treatment Outcome Of Neuroblastoma and Other Peripheralmentioning
confidence: 99%
“…SEER data are useful in identifying the disparity in cancer outcome and treatment used because SEER has different socioeconomic and outcome data (Ognjanovic et al, 2009;Sultan et al, 2009;Cheung et al, 2010;McDowell et al, 2010;Pappo et al, 2010;Bhatia, 2011;Perez et al, 2011) (Harlan et al, 1995;Shavers et al, 2003;Wampler et al, 2005;Gross et al, 2008;Lund et al, 2008;Downing et al, 2010;Martinez et al, 2010;Schlichting et al, 2012;Yao et al, 2012). In particular, SEER data have outcome and socio-economic data associated with bronchioaveolar lung cancer (Hasan et al, 2004;Saeed et al, 2012).…”
Section: Discussionmentioning
confidence: 99%